1989
DOI: 10.1098/rspb.1989.0030
|View full text |Cite
|
Sign up to set email alerts
|

Ocular vergence under natural conditions. I. Continuous changes of target distance along the median plane

Abstract: Horizontal binocular eye movements of four subjects were recorded with the scleral sensor coil - revolving magnetic field technique while they fixated a natural target, whose distance was varied in a normally illuminated room. The distance of the target relative to the head of the subject was changed in three ways: ( a ) the target was moved manually by the experimenter; ( b ) the target was moved manually by the subject; ( c ) the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(19 citation statements)
references
References 28 publications
(18 reference statements)
1
17
0
1
Order By: Relevance
“…system to track. This follows from results by Erkelens et al (1989), who showed that errors between gaze and a moving target are Ͻ1°in the depth direction for movement velocities in the range between 10 and 40°/s. Therefore, we conclude that the different lead time of gaze relative to the finger for the frontal plane and for depth reflects differences in the dynamics of visuomotor control for version and vergence.…”
Section: Discussionmentioning
confidence: 66%
“…system to track. This follows from results by Erkelens et al (1989), who showed that errors between gaze and a moving target are Ͻ1°in the depth direction for movement velocities in the range between 10 and 40°/s. Therefore, we conclude that the different lead time of gaze relative to the finger for the frontal plane and for depth reflects differences in the dynamics of visuomotor control for version and vergence.…”
Section: Discussionmentioning
confidence: 66%
“…However, numerous studies have provided results that argue against this view. Vergence velocities are greater than what would be predicted by a linear summation of a conjugate saccade with a saccade-free vergence movement, while conjugate velocities are decreased Mays 2003, 2005a;Collewijn et al 1995Collewijn et al , 1997Enright 1984Enright , 1992Erkelens et al 1989; Kenyon et al 1980;Kumar et al 2005;Maxwell and King 1992;Ono et al 1978;Oohira 1993;Zee et al 1992). Moreover, the amount of vergence facilitation is dependent on peak saccadic velocity (Busettini and Mays 2005a).…”
Section: Introductionmentioning
confidence: 83%
“…Such omnipresence of saccades during symmetrical vergence in our study is compatible with previous observations, even though this had not been quantified in detail. Erkelens et al [15] observed that symmetrical vergence was primarily smooth but often accompanied by small saccades. In the study by Zee et al [62], many pure vergence trials were contaminated by Other notations as in Table 3.…”
Section: Proportion Of Saccades During Symmetrical Vergencementioning
confidence: 98%
“…Such disconjugacy during horizontal saccades appears to be an epiphenomenon that may be due to different mechanical properties of the lateral and medial rectus muscles [9], or to a timing difference of premotor signals due to the presence of the abducens internuclear neurons intercalated between burst neurons and medial rectus motoneurons [31,62]. Reciprocally, when a symmetrical vergence is required along the median plane (where no change in version is required), small saccades occur in most cases [11,15,62]. The function of these saccades is still under debate.…”
Section: Introductionmentioning
confidence: 97%